How kinetic property shapes novelty perceptions - KIM, Junghan (Institutional Knowledge at Singapore Management University, 2015)
This article demonstrates a new substantive finding: that kinetic property in advertising, defined as direction changes in the paths of moving on-screen ad elements, enhances consumer judgments of product novelty. Across six studies, the authors first outline an inference-based theory as to why the novelty-enhancing effect of kinetic property manifests: kinetic property generates impressions of how visually lively an ad is, which leads to inferences of product atypicality and, consequently, higher novelty judgments. Second, they demonstrate boundary conditions by showing that (1) the positive effect for kinetic property is evident with incremental (and not radical) innovations, (2) the effect dissipates when figure-ground contrast in the ad makes kinetic property less discriminable, (3) contextual adaptation to kinetic property can mitigate this effect, and (4) kinetic property enhances novelty judgments primarily when product category characteristics such as perceived market dynamism match with kinetic property-based executions. The authors offer substantive implications for firms marketing new products as well as for multimedia advertising.